Peculiar form of cerebral microdysgenesis characterized by white matter neurons with perineuronal and perivascular glial satellitosis: A study using a variety of human autopsied brains - Arai, Nobutaka; Umitsu, Reiko; Komori, Takashi; Hayashi, Masaharu; Kurata, Kiyoko; Nagata, Jinro; Tamagawa, Kimiko; Mizutani, Toshio; Oda, Masaya; Morimatsu, Yoshio (Pathology international, 2003)
Microdysgenesis (MD) is a neuropathological term that implies a variety of minor developmental abnormalities of the brain. Recently, MD has been used for pathological diagnosis of cerebral tissues surgically resected from epileptic patients. However, criteria or consensus on pathological diagnosis of MD is still vague and controversial because of the lack of control studies. Therefore, this study paid special attention to the presence of white matter neurons with perineuronal glial satellitosis (WMN‐GS) and perivascular glial satellitosis (PVGS) in the white matter, which are occasionally observed in epileptic foci, in order to clarify whether they could be handled as definite findings of MD. The materials included 80 autopsied whole brains ranging from normal subjects to patients with cerebrovascular disorder, neurodegenerative diseases and malformations. In each case, the presence of WMN‐GS and/or PVGS was searched in 10 gyri in all five lobes (rostral frontal lobe, caudal frontal lobe, parietal lobe, temporal lobe and oc‐cipital lobe) and evaluated. Statistically significant, WMN‐GS and/or PVGS preferentially appeared in a diseased group consisting of neuronal migration disorder and related conditions, such as polymicrogyria, nodular heterotopia or tuberous sclerosis, leading to a suggestive conclusion that the presence of WMN‐GS and/or PVGS could be a peculiar form of MD possibly derived from neuronal migrational arrest or related events, even if they appear alone without any other gross abnormalities.